Association between kidney retransplantation and survival according to age in the French national cohort of dialysis patients. Issue 8 (24th May 2022) - Girerd, Sophie; Duarte, Kevin; Couchoud, Cécile; Laurain, Emmanuelle; Courivaud, Cécile; Bauwens, Marc; Kessler, Michèle; Frimat, Luc; Girerd, Nicolas
Abstract : The mean age of patients returning to dialysis after a first kidney transplantation (KT) has increased in the past decades. We aimed to assess the association between second KT (2KT) and survival according to age at the time of return to dialysis. Data of 5334 patients registered in the French Renal Epidemiology and Information Network (REIN) (mean age 56.6 ± 13.6 years) who returned to dialysis after a first KT were collected. The association of 2KT with death was assessed using a propensity score‐based analysis taking into account baseline and follow‐up variables. In relisted patients (3272 patients, 61.3%), retransplantation was associated with better overall survival in comparison with patients who remained in dialysis (adjusted HR 0.75 [0.63–0.89], p = .0009). The survival advantage conferred by retransplantation gradually declined with increasing age (adjusted HR 0.41 [0.24–0.70] in patients <50, HR 0.94 (0.69–1.27) in patients aged 70 or older, p for interaction 0.034 for age considered as a continuous variable). 2KT is associated with better survival as opposed to remaining on dialysis after a first kidney graft failure. Nevertheless, this survival benefit is age dependent and diminishes with increasing age. The risk/benefit ratio should be comprehensively assessed in the oldest patients when relisting is considered. Abstract : In patients who returned to dialysis after a first kidney transplantation, retransplantation compared to remaining on dialysis is associated with improved survival which, however, decreases with increased age.